2019
DOI: 10.1111/1365-2745.13220
|View full text |Cite
|
Sign up to set email alerts
|

Soil biota and chemical interactions promote co‐existence in co‐evolved grassland communities

Abstract: 1. Plant populations can exhibit local adaptation to their abiotic environment, such as climate and soil properties, as well as biotic components such as the chemical signatures of dominant plant species and mutualistic and pathogenic microbial populations. While patterns of local adaptation in individual species are widely recorded, the importance of microevolutionary processes for plant community assembly and function is poorly understood.2. Here, we examined how a history of long-term co-existence, and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Our findings reveal that the modification of the composition of the rhizosphere metabolome by early species can create historical contingency effects that affect root foraging by later arrivers in a species-specific and contextdependent manner. Our results contribute to current scientific knowledge showing that soil chemical cues can mediate plant-plant interactions and affect species coexistence (Delory et al, 2016;Semchenko et al, 2019). Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Our findings reveal that the modification of the composition of the rhizosphere metabolome by early species can create historical contingency effects that affect root foraging by later arrivers in a species-specific and contextdependent manner. Our results contribute to current scientific knowledge showing that soil chemical cues can mediate plant-plant interactions and affect species coexistence (Delory et al, 2016;Semchenko et al, 2019). Fig.…”
Section: Discussionsupporting
confidence: 70%
“…This microbial signature can remain as a legacy in the soil after the plant is gone, and in turn affect other plants growing later in the same soil (Kulmatiski et al 2008; Van der Putten et al 2013; Teste et al 2017; Eppinga et al 2018). It is often speculated that soil legacy effects created by plants play an important role in regulating plant community dynamics and plant coexistence (Lekberg et al 2018; Semchenko et al 2019). It was recently shown that inoculation of soils with biotic legacies can change plant community development under natural conditions (Wubs et al 2016; Wubs et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on plant interactions include the role that species mixtures and nurse effects play in building complex ecosystems (Padilla & Pugnaire ; Bucharova et al ), including age trends in interactions transiting from facilitation to competition (Forrester et al ). At the provenance level, locally co‐evolved neighboring plants can mutually benefit each other in terms of survival and performance when growing in close proximity, taking advantage of sympatric interactions (Grady et al ; Semchenko et al ). Even within provenances of the same species, “social” interactions among plants may have a genetic basis (referred to as indirect genetic effects), and can affect the performance of neighboring plants through, for example, competition and disease spread (Costa e Silva et al ).…”
Section: Introductionmentioning
confidence: 99%